Total Flavones of Abelmoschus manihot Remodels Gut Microbiota and Inhibits Microinflammation in Chronic Renal Failure Progression by Targeting Autophagy-Mediated Macrophage Polarization - Tu, Yue; Fang, Qi-Jun; Sun, Wei; Liu, Bu-Hui; Liu, Ying-Lu; Wu, Wei; Yee, Hong-Yun; Yuan, Can-Can; Wang, Mei-Zi; Wan, Zi-Yue; Tang, Ren-Mao; Wan, Yi-Gang; et al. (Frontiers in Pharmacology, 2020)
Background: Recently, progression of chronic renal failure (CRF) has been closely associated with gut microbiota dysbiosis and intestinal metabolite-derived microinflammation. In China, total flavones of Abelmoschus manihot (TFA), a component of Abelmoschus manihot, has been widely used to delay CRF progression in clinics for the past two decades. However, the overall therapeutic mechanisms remain obscure. In this study, we designed experiments to investigate the renoprotective effects of TFA in CRF progression and its underlying mechanisms involved in gut microbiota and microinflammation, compared with febuxostat (FEB), a potent non-purine selective inhibitor of xanthine oxidase. Methods: In vivo, the CRF rat models were induced by uninephrectomy, potassium oxonate, and proinflammatory diet, and received either TFA suspension, FEB, or vehicle after modeling for 28 days. In vitro, the RAW 264.7 cells were exposed to lipopolysaccharide (LPS) with or without TFA or FEB. Changes in parameters related to renal injury, gut microbiota dysbiosis, gut-derived metabolites, and microinflammation were analyzed in vivo. Changes in macrophage polarization and autophagy and its related signaling were analyzed both in vivo and in vitro. Results: For the modified CRF model rats, the administration of TFA and FEB improved renal injury, including renal dysfunction and renal tubulointerstitial lesions; remodeled gut microbiota dysbiosis, including decreased Bacteroidales and Lactobacillales and increased Erysipelotrichales; regulated gut-derived metabolites, including D-amino acid oxidase, serine racemase, D-serine, and L-serine; inhibited microinflammation, including interleukin 1β (IL1β), tumor necrosis factor-α, and nuclear factor-κB; and modulated macrophage polarization, including markers of M1/M2 macrophages. More importantly, TFA and FEB reversed the expression of beclin1 (BECN1) and phosphorylation of p62 protein and light chain 3 (LC3) conversion in the kidneys by activating the adenosine monophosphate-activated protein kinase-sirtuin 1 (AMPK-SIRT1) signaling. Further, TFA and FEB have similar effects on macrophage polarization and autophagy and its related signaling in vitro. Conclusion: In this study, we demonstrated that TFA, similar to FEB, exerts its renoprotective effects partially by therapeutically remodeling gut microbiota dysbiosis and inhibiting intestinal metabolite-derived microinflammation. This is achieved by adjusting autophagy-mediated macrophage polarization through AMPK-SIRT1 signaling. These findings provide more accurate information on the role of TFA in delaying CRF progression.